Continuous Transversus Abdominis Plane Block for Primary Open Inguinal Hernia Repair: A Randomized, Double-Blind, Placebo-Controlled Trial. Issue 2 (31st October 2019) - Flaherty, James M; Auyong, David B; Yuan, Stanley C; Lin, Shin-E; Meier, Adam W; Biehl, Thomas R; Helton, W Scott; Slee, April; Hanson, Neil A
Abstract: Objective: Patients undergoing open inguinal hernia repair may experience moderate to severe postoperative pain. We assessed opioid consumption in subjects who received a continuous transversus abdominis plane block in addition to standard multimodal analgesia. Design: Randomized, double-blind, placebo-controlled. Setting: Tertiary academic medical center. Subjects: Adult patients undergoing open inguinal hernia repair at Virginia Mason Medical Center. A total of 90 patients were enrolled. Methods: Subjects presenting for surgery were randomized to receive either a continuous transversus abdominis plane block or a subcutaneous sham block. The primary outcome was opioid consumption within the first 48 hours after surgery. Secondary outcomes included pain scores, activities assessment scores, and opioid-related adverse events. Multimodal analgesia utilized in both groups included acetaminophen, nonsteroidal anti-inflammatory drugs, and surgical local anesthetic infiltration. Results: Eighty-two subjects, 42 from the block group and 40 from the sham group, completed the study, per protocol. The intention-to-treat analysis demonstrated no difference in 48-hour postoperative oxycodone equivalent consumption between the block and sham groups (27.8 mg ± 26.8 vs 32 mg ± 39.2, difference –4.4 mg, P = 0.55). There was a statistically significant reduction in pain scores at 24 hours in the block group. There were no other differences in secondary outcomes. Conclusions: Continuous transversus abdominis plane blocks provide modest improvements in pain after open inguinal hernia repair but fail to significantly reduce opioid consumption or improve functional activity levels in the setting of multimodal analgesia use.